(untitled) (Research, Society and Development, 2024)
Antimicrobial resistance (AMR) has become a growing concern in animal and human health, affecting the effective treatment of bacterial infections. This study aims to review the impact of AMR in companion animals, particularly dogs and cats, and its implications for public health. The methodology used involved a narrative literature review, searching databases such as Google Scholar, PubMed, ScienceDirect and Scielo, as well as documents from international organizations such as the World Organization for Animal Health (OIE). The results indicate that the inappropriate use of antibiotics in veterinary clinics has promoted the selection of resistant bacterial strains, such as methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase (ESBL)-producing Escherichia coli, which pose risks to both animal and human health. In addition, the proximity between pets and humans facilitates the transmission of resistant microorganisms. The treatment of AMR requires an integrated One Health approach, which considers the interconnections between animal, human and environmental health. Control strategies, such as the rational use of antibiotics, the development of infection control programs in veterinary hospitals and the continuous education of veterinarians, are essential to mitigate the spread of antimicrobial resistance. The research suggests the need for more studies into alternative therapies, such as the use of probiotics and vaccines, to prevent infections and reduce dependence on antimicrobials.